THE INFLUENCE OF SOCIAL MOVEMENTS ON THE INTERNATIONAL LEGAL PROCESS: A CASE STUDY OF THE ISRAELI-PALESTINIAN CONFLICT IN THE INTERNATIONAL COURT OF JUSTICE - Mutmainnah, Fitrah Ainun (Politea : Jurnal Politik Islam, 2024)
This study examines the influence of social movements on the international legal process in the context of the Israeli-Palestinian conflict at the International Court of Justice (ICJ). The focus is on the role of the Boycott as a social movement, Divestment, and Sanctions (BDS) in mobilizing global support and influencing legal decisions through advocacy and public pressure. This study shows that social movements are important in shaping public opinion and driving social change. The use of social media by the BDS movement is explained as an effective mobilization tool in disseminating information and organizing solidarity actions. A case study related to the opinion of the ICJ adviser on Israel's separation wall illustrates how international pressure from social movements can affect legal proceedings. The findings of this study provide new insights into the dynamics of the interaction between social advocacy and legal decisions, as well as their implications for the Israeli-Palestinian conflict and international law. This research contributes to understanding the important role of social movements in influencing international legal decisions and offers more effective strategies to support human rights and justice